COMMON FIXED POINT IN 𝐺-METRIC SPACES VIA GENERALIZED Γ-𝐶_𝐹 -SIMULATION FUNCTION - S. V. Puvar; R. G. Vyas (Проблемы анализа)
We present the generalized Γ-𝐶_𝐹 -simulation function and establish the common fixed point result for weak (𝜂_𝐹 , 𝑔) q-contraction in complete 𝐺-metric space. The exploration extends to its ramifications on both quasi-metric spaces and metric spaces. The study explores the existence of a solution for a non-linear integral equation as an application of these results.